Faktor-Faktor yang Mempengaruhi Minat Investasi Pasar Modal di Generasi Z - Vina Anggreani; Ngurah Pandji Mertha Agung Durya; Zaky Machmuddah; Bambang Minarso (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to find evidence of whether motivation, investment knowledge, and self-efficacy influence investment interest in the capital market among Generation Z. This study is based on the Theory of Planned Behavior (TPB). The research data is primary data obtained by distributing questionnaires to Generation Z at Dian Nuswantoro University in Semarang who have attended seminars, courses, or training on the capital market and who have made investments. The sample was determined using purposive sampling. Data collection was conducted by distributing questionnaires to 400 respondents who were selected as the research sample, while data analysis was performed using SPSS software. The results of the partial test showed that investment motivation, knowledge, and self-efficacy had a positive and significant effect on investment interest. Simultaneously, the results show that the three independent variables have a significant impact on investment interest. The coefficient of determination is 0.221, indicating that investment motivation, knowledge, and self-efficacy are significant and can explain 22.1% of the variance in results related to investment interest, with dependence influenced by variables other than those studied. The findings show that the investment motivation variable has the most dominant effect on the results. The findings show that an increase in student motivation, investment knowledge, and self-confidence is significant in increasing student investment in the capital market.